2013
DOI: 10.1177/0883073813483364
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Angiography Evidence of Vasospasm in Children With Suspected Acute Hemiplegic Migraine

Abstract: Hemiplegic migraine is a rare subtype of migraine that is differentiated by motor weakness in the aura phase. The purpose of this case series was to examine the magnetic resonance angiogram findings of patients suffering from suspected acute hemiplegic migraine. This was a retrospective institutional board review protocol study of 8 patients. All patients received full brain magnetic resonance imaging under a 1.5-T magnet. The scans were subsequently evaluated by a neuroradiologist and 2 neurologists who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…However, in their case series, only the middle cerebral artery was examined. 11 The study by Safier et al did not report on the other branch vessels of the circle of Willis. Consequently, it is not certain whether the vascular changes occurred in only the middle cerebral artery in their patients or if other vessels were similarly affected but not evaluated as part of the study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in their case series, only the middle cerebral artery was examined. 11 The study by Safier et al did not report on the other branch vessels of the circle of Willis. Consequently, it is not certain whether the vascular changes occurred in only the middle cerebral artery in their patients or if other vessels were similarly affected but not evaluated as part of the study.…”
Section: Discussionmentioning
confidence: 97%
“…The children had decreased perfusion if scanned Ͻ14 hours from the onset of symptoms, while evidence of increased perfusion was found if imaging was performed at Ͼ17 hours from symptom onset. 10 In addition, Safier et al 11 reported a series of 8 children with hemiplegic migraine who demonstrated vascular narrowing by MRA. However, in their case series, only the middle cerebral artery was examined.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, childhood AIS is rarely diagnosed within the 4.5 hours window for consideration for intravenous tissue plasminogen activator (tPA) treatment and efforts are much needed on this important issue [29]. Both pre-and post-hospital delays occur with a significant increase in time to diagnosis in outpatients versus inpatients for whom it is still nearly one day… Longer delay has also been associated with posterior circulation stroke, non-abrupt onset, milder or shorter duration symptoms, altered level of consciousness and presentation after working hours [30][31][32][33]. However, some children with large artery occlusion who are not diagnosed within 4.5 hours may theoretically still be eligible for thrombectomy.…”
Section: Limits For Pediatric Access To Recanalization Treatmentsmentioning
confidence: 99%
“…These data concord with the hyperperfusion phenomenon described during the headache phase. Data regarding MRA findings in migraine with aura are sparse and limited (8,12). Safier et al.…”
Section: Discussionmentioning
confidence: 99%
“…Literature studies describing TOF-MRA findings in migraine with aura are rare. A reversible vasospasm has been reported in an 11-year-old girl (11) and more recently in a series of eight children suffering from acute hemiplegic migraine (12).…”
mentioning
confidence: 95%